Influence of ClearT and ClearT2 Agitation Conditions in the Fluorescence Imaging of 3D Spheroids - Silva, Daniel N. (2021)
3D tumor spheroids have arisen in the last years as potent tools for the in vitro screening of novel anticancer therapeutics. Nevertheless, to increase the reproducibility and predictability of the data originated from the spheroids it is still necessary to develop or optimize the techniques used for spheroids' physical and biomolecular characterization. Fluorescence microscopy, such as confocal laser scanning microscopy (CLSM), is a tool commonly used by researchers to characterize spheroids structure and the antitumoral effect of novel therapeutics. However, its application in spheroids' analysis is hindered by the limited light penetration in thick samples. For this purpose, optical clearing solutions have been explored to increase the spheroids' transparency by reducing the light scattering. In this study, the influence of agitation conditions (i.e., static, horizontal agitation, and rotatory agitation) on the ClearT and ClearT2 methods' clearing efficacy and tumor spheroids' imaging by CLSM was characterized. The obtained results demonstrate that the ClearT method results in the improved imaging of the spheroids interior, whereas the ClearT2 resulted in an increased propidium iodide mean fluorescence intensity as well as a higher signal depth in the Z-axis. Additionally, for both methods, the best clearing results were obtained for the spheroids treated under the rotatory agitation. In general, this work provides new insights on the ClearT and ClearT2 clearing methodologies and their utilization for improving the reproducibility of the data obtained through the CLSM, such as the analysis of the cell death in response to therapeutics administration.